LELANG DI INTERNET DAN PROBLEMATIKANYA DALAM FIQIH ISLAM - Muhsinin, Mahmud (2011)
Auction on the Internet or also called an online auction business model is one in which bidding for products and services conducted via the Internet, with participants was limited. The function of buying and selling in an auction format is done through software or software that manage various auction processes. Special feature of the online auction is an auction process run by a software program or auction. Problems: problem have been the research is the diversity of model rules of online auctions. This is because there is no legal clarity and the rule of government. Each site to apply its own rules and different. Islamic Fiqh: Islamic law or the rules of Islam. Methods This study used a qualitative approach. With research data is online auction sites that exist in Indonesia. Limitation of the study period from the date of December 20, 2009 to 20 February 2010. Objective: to know the views of Islamic jurisprudence about the auction on the Internet or online auction. Results: Islamic views on online auction are 2 models: (1) online auction that works like an auction house. These sites serve as an online auction service provider for its members. Each member can make such an offer and also to auction off the goods on the site. This species is allowed in Islam, because it fulfilled the terms of auction and no element of gambling, usury, gharar and kedhaliman in the transaction process. (2) online auctions using points. These types of online auctions using points or coins as a means to make a bid. For those bidders are required to buy points in advance to be able to bid. Every time you make a bid then it will reduce one point he had. These types include the type of online auction has been prohibited by reason: there is an element of gambling in the auction process. For participants who do not win have to suffer losses with loss of points that are used when bidding.